The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/070674371405900604
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of a Rapid Response Team Intervention for Suicidal Youth Presenting at an Emergency Department

Abstract: Objective: To investigate the cost-effectiveness of a rapid response team (RRT), compared with usual care (UC), for treating suicidal adolescents. Methods:Suicidal adolescents (n = 286) presenting at an emergency department were enrolled in a trial to compare UC with enhanced outpatient care provided by an RRT of health professionals. Functioning (Child Global Assessment Scale) and suicidality (Spectrum of Suicidal Behavior Scale) scores were measured at baseline and 6 months later. Resource use and cost data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 26 publications
0
40
0
4
Order By: Relevance
“…Timely assessment strategies, including screening, were att ributes of interventions for a range of mental health problems examined in 10 of the included studies (Box 4). 47,[49][50][51][52][53][54][55][56][57] The economic evidence for such approaches was generally favourable, although there were exceptions. 52,55 Schools-based screening and prevention interventions were examined for anxiety, 58 depression, 47,53,62,63 eating disorders 52,59 and substance use disorders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Timely assessment strategies, including screening, were att ributes of interventions for a range of mental health problems examined in 10 of the included studies (Box 4). 47,[49][50][51][52][53][54][55][56][57] The economic evidence for such approaches was generally favourable, although there were exceptions. 52,55 Schools-based screening and prevention interventions were examined for anxiety, 58 depression, 47,53,62,63 eating disorders 52,59 and substance use disorders.…”
Section: Resultsmentioning
confidence: 99%
“…66,68,69 A group delivery context (including in classrooms) was an att ribute of interventions for a range of mental health problems in nine studies, 47,52,58,[60][61][62][63]70,71 again with cost-eff ectiveness evidence that varied between populations. Other att ributes of interventions examined were automated processes, 63 case management, 48,50,65-67 crisis response, 51 fi nancing, 72 holistic care approaches, 48,58,72 information provision, 54,57,61,62,67,69,71 peer support and mentoring 57,71 and staff training and support 49 (Box 4).…”
Section: Resultsmentioning
confidence: 99%
“…As noted before, many regions rely on general emergency or pediatric emergency departments for such care. One study found that a rapid response team of behavioral experts who supported a pediatric emergency department was both clinically effective and was able to provide substantial cost savings to the institution [46]. Urgent psychiatric consults to medical and pediatric EDs are another recently studied option and have had similar positive results [47].…”
Section: New Service Designsmentioning
confidence: 99%
“…Additional interventions include the use of rapidresponse teams to link suicidal emergency department patients to outpatient services (Greenfield, Lawson, Hechtman, Rousseau, & Platt, 2002;Latimer, Gariepy, & Greenfield, 2014), dialectical behavior therapy (Katz, Cox, Gunasekara, & Miller 2004;Rathus & Miller, 2002), multisystemic therapy (Huey et al, 2004), skills-based treatment (Donadlson, Spirito, & Esposito-Smythers, 2005), individual cognitive-behavioral therapy (Esposito-Smythers, Spirito, Kahler, Hunt, & Monti, 2011), and crisis hotlines for urgent counseling (Gould, Cross, Pisani, Munfakh, & Kleinman, 2013).…”
Section: Indicated Prevention Programs Indicated Approaches Targetinmentioning
confidence: 99%
“…The rapid response model was more cost-effective as a method for linking suicidal adolescents to outpatient care as compared to usual care practices, as a result of the reduced rate of hospitalizations (Latimer, Gariepy, & Greenfield, 2014).…”
Section: Indicated Prevention Programs Indicated Approaches Targetinmentioning
confidence: 99%